2004
DOI: 10.1373/clinchem.2004.031690
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Modified Albumin Concentrations in Patients with Peripheral Vascular Disease and Exercise-Induced Skeletal Muscle Ischemia

Abstract: Background: Ischemia-modified albumin (IMA) is a new marker of myocardial ischemia, there is concern that IMA concentrations may be affected by ischemia occurring in tissues other than the myocardium. Methods: We assessed 23 consecutive patients (15 males; mean age, 67 years) with typical leg claudication and documented peripheral vascular disease (PVD). All patients underwent both treadmill-exercise stress testing to induce leg ischemia and dobutamine stress echocardiography 1 week apart for the assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 20 publications
(19 reference statements)
4
56
0
3
Order By: Relevance
“…Molecular markers that are able to improve diagnosis are required to reduce ACVD mortality. IMA, derived from human serum albumin (HSA), is an important molecular marker in cardiac care due to its association with ischemic events (19). The amino-terminal sequence of HSA, which is unique to humans, is the major binding site of transition metals, including Co, Cu and Ni.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers that are able to improve diagnosis are required to reduce ACVD mortality. IMA, derived from human serum albumin (HSA), is an important molecular marker in cardiac care due to its association with ischemic events (19). The amino-terminal sequence of HSA, which is unique to humans, is the major binding site of transition metals, including Co, Cu and Ni.…”
Section: Discussionmentioning
confidence: 99%
“…Middleton et al generated similar results in a study conducted in the London marathon in 2004 [16]. Roy et al observed that IMA levels during muscle ischemia caused by exercise decreased below basal levels [17]. Piechota et al [5] detected a reduction in IMA levels after exercise in patients previously diagnosed with coronary atherosclerosis.…”
Section: Ischemia-modified Albumin Levels In Soccer Playersmentioning
confidence: 75%
“…One of the issues debated in this context is lactate interference. It has been reported that lactate levels, which increase due to exercise, reduce IMA values [17,18].…”
Section: Ischemia-modified Albumin Levels In Soccer Playersmentioning
confidence: 99%
“…Isc he mi a mo di fied al bu min (IMA) me a su re ment re fer red as al bumin co balt bin ding test (ACB) is a new bi o mar ker of car di ac isc he mi a, ske le tal musc le isc he mi a and ce reb ral isc he mi a. [13][14][15] To in ves ti ga te the cli ni cal uti lity of IMA as a se rum mar ker for MTBI, we attemp ted to eva lu a te the ro le of IMA in rats with clo sed he ad MTBI.…”
Section: Ischemia Modified Albumin Levels Following Mild Closed Head mentioning
confidence: 99%